The Art Déco Influence in the Modern Turkish Architecture of the Early Republican Period (Prostor, 2022)
With the proclamation of the Republic, Atatürk, the founder of Modern Turkey, wanted a new model of politics that would bring about the establishment of the “nation state”, also symbolized by architecture. Having decided to make a transition to modern architecture in Turkey, Atatürk invited academics from Germany and Vienna to achieve this. Consequently, by the 1930s, architecture followed a functionalistrationalist path in both public buildings and in residences. Another architectural style that wielded a lot of influence on the trends in the Modern Movement in this period was Art Déco. The plastic effect of mass in Art Déco was accompanied by purism. The purpose of th is article is to explore the characteristics of the Art Déco style in modern Turkish architecture, tracing it back to the 1930s, the time when a culture of architecture first began to form in Turkey, as Art Déco, in combination with rationalism, proved to be an influential force in Republican Turkey. The effect of this style on the composition of structural masses shall be described through examples of public and residential buildings. At the same time, an attempt shall be made to explore the connotations of contemporaneity, progress, technology, and industry as expressed in the vocabulary of the Republican ideology that embraced the mass aesthetic of the formal style that was Art Déco.